Gender disparities in Universiti Teknologi MARA students’ mental wellness: A comparative study - Syarifah Norhuda Syed Wahid; Azwan Shah Aminuddin; Hazlin Hasan; Khairunisa Nikman; Nurfarawahidah Badruesham (Institute of Advanced Engineering and Science, 2023)
The COVID-19 pandemic has severely affected the wellbeing of people worldwide, especially the younger population, primarily students, who are ill-equipped to cope with the new norm. The need to adapt to the new learning methods has created greater difficulties. Previous research stated that altered life routine and upsetting life events have led to psychological disorders like depression, anxiety, and stress, with females experiencing higher degrees of disorder. With the objectives to further investigate the escalating students’ mental wellbeing issues, the researchers focused on gender comparison among Universiti Teknologi MARA (UiTM) students. There were 1,931 students from all UiTM campuses answered Depression, Anxiety and Stress Scale 21 (DASS-21) questionnaire online to test their levels of depression, anxiety and stress while attending online distance learning (ODL) classes. Descriptive and independent t-test analyses were performed using IBM-SPSS AMOS version 24 software. The result indicated that both genders’ levels of depression and stress were normal but most females experienced an extremely severe anxiety level. There also existed significant differences at 5% level of significance between the genders for anxiety and stress disorder levels. The findings are hoped to provide relevant authorities a better understanding on the appropriate intervention approaches focusing on gender to alleviate the COVID-19 impacts and prevent potential declines in the students’ wellbeing.